PERANCANGAN DESTINATION BRANDING WISATA COBAN TALUN SEBAGAI UPAYA MEMBANGUN BRAND RECALL - Priyambudi, Eko; Yurisma, Dhika Yuan; Fahminnansih, Fenty (Jurnal Art Nouveau, 2018)
Researchers make direct observations and found that Coban Talun tourism does not have a logo or visual identity that can describe the potential or natural wealth in this tour. In this design, researchers will focus on the logo design process in the goal branding effort.The concept of a logo that has been designed is impressive from data and keyword analysis. The concept is to give a great impression to the tourists who visit this tour by making a visual identity that describes the potential and natural wealth of this tour.In addition to creating logos, the design also designs brand guidelines that aim to provide an explanation of the value and essence of the Coban Talun brand along with guidelines for the use of their logos and applications for design execution. Implementation of designs on stationary sets and promotional media such as designed brochures, x-banners and merchandises intended as an informative medium that can help target audiences in knowing the brands of Coban Talun.